Market Potential, Farmer Preferences, and Awareness of Hybrid Cotton in Warangal District of Telangana State, India - Sai Tejaswini Puli; Srilatha Challa; Radhika Pagadala; Supriya K (Archives of Current Research International, 2025)
Aim of the Study: The study aimed to analyze the market potential and assess the awareness and preference levels of farmers and retailers towards Rasi Swift (RCH 971) cotton hybrid in Warangal district. The objective was to understand adoption patterns, identify influencing factors, and develop strategies to increase market share for Rasi Seeds Pvt. Ltd. Study Design, Area, and Duration: This was a descriptive study conducted in Warangal district of Telangana state. The study was carried out over a period of four months during the Kharif 2024 season, covering four mandals: Damera, Chennaraopet, Narsampeta, and Thorrur. From each mandal, two villages were purposively selected based on area under cotton cultivation. Methodology: A multistage sampling technique was adopted. Primary data was collected from a total of 80 respondents, including 60 farmers (users and non-users of Rasi Swift) and 20 retailers using structured interview schedules. Percentage analysis and independent t-tests were used to compare awareness and preference levels between users and non-users. Market potential was estimated based on cotton area and seed requirement (2 packets per acre), while sales data from retailers helped calculate current market share. Results: The study revealed that Rasi Swift currently holds a market share of approximately 49.58 percent in the cotton seed market of Warangal district. Among the surveyed farmers, the awareness level of Rasi Swift was high, especially among users, who cited its early maturity, high yield potential, and boll size as the major reasons for preference. Retailers also demonstrated strong awareness and confidence in the brand, with 100% of them expressing willingness to sell it again in future seasons. The major sources of awareness were company representatives and farmer feedback, which played a critical role in influencing seed choices. A comparative analysis using t-tests showed that both awareness and preference levels were statistically higher among Rasi Swift users than non-users. Sales records from eight selected villages indicated 11,850 packets sold, while the total cotton seed requirement was 23,900 packets, leaving nearly 50.42 percent of the potential market untapped. The estimated seed requirement was based on standard sowing practices of 2 packets per acre, with cotton acreage totalling 11,450 acres across sample villages. The hybrid was also favored by retailers due to better margins and repeat demand. These findings collectively suggest that strategic promotion, wider demonstration, and stronger supply chain engagement could further improve market penetration.